Researching and Writing Dissertations in Hospitality and Tourism - Clark, Mona; Riley, Michael ;Wilkie, Ella ;Wood, Roy C. (London, United Kingdom : International Thomson Business Press, 1999)
"This book is a comprehensive guide to all aspects of researching and writing dissertations in hospitality and tourism."--Jacket.
Getting started -- Key qualitative research methods -- Key statistical and quantitative techniques -- Writing your dissertation.
Includes bibliographical references and index.
Keywords: DISSERTATIONS, ACADEMIC